Notes on the Global Well-Posedness for the Maxwell-Navier-Stokes System - Ensil Kang; Jihoon Lee (Abstract and Applied Analysis)
Masmoudi (2010) obtained global well-posedness for 2D Maxwell-Navier-Stokes system. In this paper, we reprove global existence of regular solutions to the 2D system by using energy estimates and Brezis-Gallouet inequality. Also we obtain a blow-up criterion for solutions to 3D Maxwell-Navier-Stokes system.